Case Report: Secondary syphilis with pulmonary involvement mimicking eosinophilic granulomatosis with polyangiitis — targeted next-generation sequencing as an adjunct in resolving an atypical non-exanthematous presentation - Shunjun Tang; Tiehan Zhang; Aiyi Hao; Bin Su; Bin Liu (Frontiers in Medicine, 2026)
Background The global resurgence of syphilis poses growing challenges for clinical diagnosis, particularly when atypical presentations without classic mucocutaneous lesions mimic systemic autoimmune diseases. Pulmonary involvement in secondary syphilis is rare and frequently misdiagnosed, leading to inappropriate immunosuppressive therapy. Case presentation A 24-year-old male presented with one month of inflammatory back pain and two weeks of cough, purulent sputum, and intermittent low-grade fever. He initially denied high-risk sexual exposure. Physical examination revealed no rash, chancre, or lymphadenopathy. Laboratory workup showed marked eosinophilia (15.70%), elevated C-reactive protein, and immunoglobulin E (1,290 IU/mL). Chest computed tomography demonstrated bilateral patchy infiltrates and multiple small upper-lobe nodules. While this presentation suggested eosinophilic granulomatosis with polyangiitis (EGPA), unexpected positive syphilis serology (rapid plasma reagin 1:128) redirected the diagnostic workup. Upon further confidential questioning, the patient acknowledged high-risk sexual exposures. Bronchoalveolar lavage fluid targeted next-generation sequencing (tNGS) detected a high load of Treponema pallidum (11,732 reads) alongside co-infecting respiratory pathogens. EGPA was rendered highly unlikely by complete clinical and radiological resolution following antimicrobial therapy alone, without corticosteroids. Conclusion This case illustrates that non-rash secondary pulmonary syphilis can closely mimic EGPA, and that tNGS provides a valuable adjunctive tool for resolving such diagnostic challenges, thereby preventing potentially harmful immunosuppressive treatment. As syphilis continues to re-emerge globally, clinicians should maintain a high index of suspicion for syphilitic pulmonary involvement in patients with unexplained eosinophilia and pulmonary infiltrates, even in the absence of dermatological manifestations.